Diseño de un sistema de control para el proceso de generación de aire comprimido a presión constante mediante compresor de tornillo de la minera MINCAMPA S.A.” - Cabrera Patiño, Jorge Eduardo (2020)
This thesis project addresses the design and evaluation by simulation of a conventional control system for the process of generating compressed air at constant pressure using an Atlas Copco GA 75 double screw compressor of the Mincampa S.A. located in Campanillas. This controller allows the operator to keep the air tank outlet pressure fixed at a certain point based on the mathematical model of the plant. To achieve this, a general review was made and bibliography was selected corresponding to the design of compressed air networks, mathematical modelling and experimental identification of industrial processes, data acquisition with LabVIEW™, Matlab® Simulink® tools used for the design and simulation of conventional controllers. After, the facilities for the compressed air network were redesigned according to the needs of the Mining Company and it was determined whether the existing compressor meets the appropriate requirements to meet said demand. Next, the acquisition of experimental data was carried out using a virtual instrument (VI) of the LabVIEW™ software, and then, through the Matlab® system identification technique, to determine the mathematical model that describes the behaviour of the process. Subsequently, in the Matlab® environment through the use of Simulink® tools, the appropriate control algorithm for the dynamics of the mathematical model of the plant under study was developed. Finally, a cost-benefit analysis was carried out to determine if the proposal for future implementation of this control system in the compressed air generation process of the Mincampa S.A. Keywords: Data acquisition, compressed air, screw compressor, system identification, constant pressure, control system.